The Role of Dyslipidemia in Periodontitis - Bitencourt, Fernando Valentim; Nascimento, Gustavo G.; Costa, Susilena Arouche; Orrico, Silvana Regina Perez [UNESP]; Ribeiro, Cecilia Claudia Costa; Leite, Fábio Renato Manzolli (MDPI, 2023)
Studies have suggested an important role of dyslipidemia, a condition with alterations in blood lipid levels, in promoting an additional effect on periodontal breakdown. Thus, this study aimed to explore the theoretical pathways associated with dyslipidemia and periodontitis. We used data from 11,917 US adults with complete periodontal examinations participating in the Third National Health and Nutrition Examination Survey (NHANES III). Our hypothesis was tested using structural equation modelling (SEM). Dyslipidemia was defined according to the National Cholesterol Education Program (NCEP-ATP III) and periodontitis as a latent variable reflecting the shared variance of the number of surfaces with periodontal pocket depth [PPD] = 4 mm, PPD = 5 mm, PPD ≥ 6 mm, clinical attachment level [CAL] = 4 mm, CAL = 5mm, CAL ≥ 6 mm, and furcation involvement. The model also considered distal determinants (age, sex, and socioeconomic status) and proximal determinants (HbA1c, smoking and alcohol consumption, and obesity). The model showed sufficient global fit (Root Mean Squared Error of Approximation = 0.04, 90%CI = 0.04–0.05, Tucker–Lewis Index = 0.93, Comparative Fit Index = 0.95). Age, sex, socioeconomic status, obesity, and smoking were directly associated with periodontitis (p < 0.01). Dyslipidemia revealed a significant direct effect on periodontitis (standardized coefficient [SC] = 0.086, SE 0.027; p < 0.01), also mediated via an indirect pathway through HbA1c (SC = 0.021; SE 0.010; p = 0.02) and obesity (SC = 0.036; SE 0.012; p < 0.01) and resulted in a total effect on periodontitis. Dyslipidemia was associated with periodontitis through a direct pathway and indirectly through HbA1c and obesity in the US population. These results support the need for a multi-professional approach to tackling oral and noncommunicable diseases (NCDs), directed at their common risk factors.
Keywords: diabetes mellitus; dyslipidemias; non-communicable diseases; periodontal diseases; public health dentistry; systemic disease